Advances in biological conversion technologies: new opportunities for reaction engineering. Issue 4 (3rd March 2020) - Woodley, John M.
Abstract : Reaction engineering needs to embrace biological conversion technologies, on the road to identify more sustainable routes for chemical manufacture. Abstract : Reaction engineering needs to embrace biological conversion technologies, on the road to identify more sustainable routes for chemical manufacture. There are new options in biological conversion including modifying the properties of an enzyme by protein engineering, a pathway by metabolic engineering or a microbial host cell. However, here also lies the challenge of a multitude of technologies and modes of operation, which the reaction engineer must navigate successfully in order to implement a new process. This perspective summarizes some of the recent developments in the field and the implications for reaction engineering, with a focus on sustainable chemical production.